A Subregional Analysis of Epidemiologic and Genetic Characteristics of Influenza A(H1N1)pdm09 in Africa: Senegal, Cape Verde, Mauritania, and Guinea, 2009–2010 - Dia, Ndongo (The American Society of Tropical Medicine and Hygiene, 2013)
During the pandemic 2009 episode, we conducted laboratory-based surveillance in four countries from West Africa: Senegal, Mauritania, Cape Verde, and Guinea. Specimens were obtained from 3,155 patients: 2,264 patients from Senegal, 498 patients from Cape Verde, 227 patients from Mauritania, and 166 patients from Guinea; 911 (28.9%) patients were positive for influenza, 826 (90.7%) patients were positive for influenza A, and 85 (9.3%) patients were positive for influenza B. Among the influenza A positives, 503 (60.9%) positives were H1N1pdm09, 314 (38.0%) positives were H3N2, and 9 (1.1%) positives were seasonal H1N1. The highest detection rate for seasonal influenza viruses (17.1%) occurred in the 5–14 years age group. However, for A(H1N1)pdm09, the detection rate was highest in the 15–24 years age group (35.8%). Based on the present study data, the timeline of detection of A(H1N1)pdm09 viruses in these four countries should be Cape Verde, Guinea, Mauritania, and finally, Senegal. Genetic and antigenic analyses were performed in some isolates.